EVALUATION OF MICROCYTIC HYPOCHROMIC ANEMIA BY ELECTROPHORESIS FOR HEMOGLOBINOPATHIES IN YOUNG POPULATION - SINGH, UTKARSHA; SAXENA, PRIYANKA; BIDWAI, ATUL KUMAR; SINGH, MADHURIMA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: Hemoglobinopathies are serious genetic blood disorders requiring lifelong blood transfusions and treatment in its most severe and chronic form. If undiagnosed or untreated, these disorders ultimately lead to death. South Asia especially India, Pakistan, and Bangladesh has high populations of hemoglobinopathies. In India, there are an estimated 100,000 thalassemia majors patients and nearly 3.5 to 4 million carriers of this genetic disorder. Tribal populations in India have a range of 5–40% sickle cell anemia (SCA) sufferers. The aim of the study was to detect hemoglobinopathies by electrophoresis in microcytic hypochromic anemia in young population in the area covered by tertiary care center at Index Medical College and Hospital. Methods: A cross-sectional study was carried out in a hospital in rural area of Indore on young patients (10–30 years age group) who attended outpatient department from June 2018 to March 2020. Total 517 cases of moderate to severe anemia were included in the study. All cases were subjected to a series of hematological investigations, which include complete hemogram, peripheral blood smear, and some standard procedures. Sysmex XS800i fully automated Cell counter was used for complete blood count. It is the 5-part differential instrument. It reports on all the five subpopulations, namely, neutrophils, eosinophils, basophils, monocytes, and lymphocytes. A blood smear is a blood test used to look for abnormalities in blood cells. Results: In the study, out of 517 cases 34.4% cases were positive on Hb electrophoresis and 65.6% were negative. On electrophoresis, the number of sickle cell anemia cases was 34.3%, sickle cell trait – 20.8%, sickle beta-thalassemia – 29.8% and beta-thalassemia major – 29.8% was observed. In hemoglobinopathies, of the 73 females, 28.8% were having beta-thalassemia trait, 27.4% were having SCA 23.3% were having sickle beta-thalassemia, and 20.5% were having sickle cell trait. Of the 105 males, 30.5% were having beta-thalassemia trait, 9.5% were having sickle beta-thalassemia, 39.0% were having SCA, and 21.0% were having sickle cell trait. Conclusion: The ANMs, ASHA, and Anganwadis should be taught about the importance of screening of hemoglobinopathies. So that they can explain the purpose of screening to the female during pregnancy and to the families in the rural areas. At primary level, the CHCs and PHCs should be equipped with instruments for basic testing of hemoglobinopathies.